2010
DOI: 10.1111/j.1399-5618.2009.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts in bipolar I and bipolar II disorder: a review and meta‐analysis of the evidence

Abstract: Objective The prevalence of suicide attempts (SA) in bipolar II disorder (BPII), particularly in comparison to the prevalence in bipolar I disorder (BPI), is an understudied and controversial issue with mixed results. To date, there has been no comprehensive review of the published prevalence data for attempted suicide in BPII. Methods We conducted a literature review and meta-analysis of published reports that specified the proportion of individuals with BPII in their presentation of SA data. Systematic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
191
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(209 citation statements)
references
References 56 publications
16
191
0
2
Order By: Relevance
“…Many research studies argued that mortality rate is high among people admitted to hospitals with bipolar disorder. High risk for suicidality is not only limited to those diagnosed with bipolar I disorder rather a metaanalysis of 15 studies by Novick and Swartz [1] suggested that bipolar I and bipolar II disorder did not differ with regard to rates of attempted suicide. Approximately 2% lifetime prevalence of bipolar I disorder is [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies argued that mortality rate is high among people admitted to hospitals with bipolar disorder. High risk for suicidality is not only limited to those diagnosed with bipolar I disorder rather a metaanalysis of 15 studies by Novick and Swartz [1] suggested that bipolar I and bipolar II disorder did not differ with regard to rates of attempted suicide. Approximately 2% lifetime prevalence of bipolar I disorder is [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to the research, the majority of patients with BD deal with chronic unemployment and absenteeism from their workplace for a long periods because of their illness, or they maintain their careers while showing deterioration in their occupational functioning [5]. About fifty percent of BD patients attempt suicide and 6-20% of them die by suicide [6]. With respect to suicide, BD is a serious mental illness that has heavy impacts on the individual and society.…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the numbers of persons involved, counts of deaths per year due to suicide or other violence and that associated with medical illnesses are about the same (27). In turn, much of the excess mortality in bipolar disorder is strongly associated with its depressive components, with highest risks associated with current or past mixed-states (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Such delay is particularly ominous given the very high rate of suicide among both type I and type II bipolar disorder patients (ca. 0.36%/year, with a male:female ratio of approximately 1.6 [0.44/0.28]), with standardized mortality ratios (SMRs) estimated at over 20 times above rates in the general population (0.36/0.015=24) (21)(22)(23)(24)(25). In addition, ratios of attempts/suicides (A/S) are much lower in bipolar disorder than in the general population, reflecting greater lethality of methods and intent (25,26).…”
mentioning
confidence: 99%